Mr Peter Bakker, President and CEO of the World Business Council for Sustainable Development (WBCSD) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Inaugural meeting of the Global Alliance for Climate-Smart Agriculture. New York, 24 September 2014. Find out more: http://www.climatesmartagriculture.org